Pengaruh Ice Breaking Terhadap Motivasi Belajar Siswa Kelas IV pada Mata Pelajaran Muatan Lokal: Bahasa Simalungun di UPTD SDN 122401 Kota Pematangsiantar - Saragih, Ulva Maryani; Betty Simanjuntak, Eva (Indo-MathEdu Intellectuals Journal, 2024)
Through a preliminary study on students' motivation levels toward the Simalungun local content subject, it was found that the motivation level of students towards the Local Content Subject (Simalungun Language) was relatively low. The aim of this research is to determine the influence of icebreaking on students' motivation levels in the local content subject (Simalungun Language) at UPTD SDN 122401 in the city of Pematangsiantar. This research is quantitative in nature, and the method employed is an experimental method with the research design of "one group pretest posttest design." The population in this study consists of all fourth-grade students in UPTD SDN 122401 Pematang Siantar, totaling 33 students. Data collection techniques include questionnaires and observations. The research procedure involves preparation, pre-test, treatment, post-test, data analysis, and interpretation of results. Based on the homogeneity test, the obtained significance value (Sig.) Based on Mean is 0.08 > 0.05, concluding that the pretest and posttest data variances are homogeneous. The t-test result shows a significance value of p (sig(2-tailed) = 0.001, as p < 0.05, rejecting Ho or accepting Ha. It can be stated that there is a significant influence of icebreaking on students' motivation in the Simalungun language local content subject